PENINGKATAN KUALITAS PEMBELAJARAN GURU PAI MELALUISUPERVISI BERDIFERENSIASI DI MI MA’ARIF KUTOWINANGUN SALATIGA - Agung Dermawan, Yudi; Hariyadi, Rahmat (LPPM STAI Muhammadiyah Probolinggo, 2025)
This study aims to examine the implementation of differentiated supervision as an effort to improve the quality of Islamic Religious Education (PAI) teacher learning at MI Ma'arif Kutowinangun Salatiga. The study used a descriptive qualitative approach with data collection through observation, interviews, and documentation. The results of the study indicate that differentiated supervision is implemented by adjusting the needs, experiences, and competency levels of each teacher. This approach involves various strategies, such as clinical, collaborative, and independent supervision, which are designed to improve teacher pedagogical skills and professionalism. The positive impacts of this supervision include increasing teacher competence in designing and implementing more effective learning, increasing teacher motivation and self-confidence, and forming a collaborative work culture in the madrasah environment. Differentiated supervision also encourages the continuity of teacher professionalism through ongoing mentoring and evaluation. Thus, this approach has proven to be an effective strategy to support improving the quality of learning and education as a whole.